RESILIENCE MODEL IN TOURISM: RISK MANAGEMENT STRATEGIES TO FACE CRISES AND CHALLENGES - Marbawi; Aiyub Yahya; Nurfaliza (PT. Radja Intercontinental Publishing, 2023)
The tourism industry is increasingly vulnerable to various crises and challenges that can disrupt operations, damage destination reputations, and threaten the sector's sustainability. This study aims to propose a resilience model in tourism that integrates risk management strategies to face crises and challenges. Through an in-depth literature review, this research identifies the limitations of traditional tourism risk management approaches and explores the potential of innovative strategies in building resilience. Key factors influencing the successful implementation of the resilience model, such as effective governance, strong leadership, and knowledge management, are also discussed. The proposed resilience model emphasizes a holistic and collaborative approach, with key components including risk and vulnerability assessment, development of adaptive and innovative capacities, multi-stakeholder collaboration, proactive strategy planning and implementation, and continuous monitoring and learning. This research contributes theoretically by expanding the understanding of tourism resilience and offers practical implications for stakeholders in developing effective risk management strategies. Despite limitations such as reliance on literature review and the conceptual nature of the proposed model, this study provides a solid foundation for further exploration of resilience in tourism. The findings highlight the importance of adopting a more proactive, collaborative, and long-term perspective in tourism risk management to build resilience and ensure the sector's sustainability in the face of increasingly complex crises and challenges.